Emerging Biomedical Applications of Carbon Dot and Polymer Composite Materials - Gareeballah Osman Adam; Shazid Md. Sharker; Ji Hyun Ryu (Applied Sciences, 2022)
Carbon dot-based composite materials have been extensively developed for versatile biomedical applications, such as drug delivery, tissue engineering, bioimaging, biosensors, and photothermal cancer therapy, owing to their excellent mechanical properties, electrical and thermal conductivity, large surface-to-volume ratio, and biocompatibility. For instance, the hydrophobicity and delocalized π-electrons of carbon dots enable insoluble drug loading in carbon composite-based drug delivery carriers. In addition, carbon dot-based materials are suitable for optical and electrochemical biosensor applications owing to their intrinsic properties. Thus, this review briefly focuses on the following: (1) general aspects, (2) various sources, and (3) versatile biomedical applications of carbon dots and composite materials. More importantly, we present the emerging applications of carbon dot-based materials, such as in agricultural systems, COVID-19 theranostics, counterfeit, and security.